Proses Komunikasi Antara Budaya Dalam Pernikahan Adat Di Kelurahan Kota Medan Kabupaten Bengkulu Selatan - Fiqhri Habib Effendi; Sapta Sari; Vethy Octaviani (Jurnal Multidisiplin Dehasen (MUDE), 2024)
The aims of this study to determine the Intercultural Communication Process in Traditional Marriage in Kota Medan Urban Village, South Bengkulu Regency. The method used in this study is qualitative descriptive research. The informants in this study amounted to 7 people consisting of 3 key informants and 4 main informants. The theory used in this study was the Theory of Intercultural Communication Process Aloliliweri, 2011:44. The results of the study show that: 1. Openness of Intercultural Marriage in marriage, the way of communicating uses or uses Indonesian, but occasionally there is the use of Javanese or pesemah language in the marriage so that everyone understands and understands more quickly in the implementation of the marriage. 2. Empathy There was mutual assessment of the couple and criticism of the decisions made by the couple in deciding something for the better in the future in the household. Each couple has a commitment in marriage, especially the problem of residence, some follow their husbands and some still live in their in-laws' house because of other circumstances and considerations. 3. Positive Attitude (positiveness) in a family, praise was reduced to please their partner in terms of dress or appearance even though it was important to add harmony to the family, it was one form of pleasant attention to their partner. 4. Supportive Attitude (supportiveness) there was mutual communication between husband and wife before taking action that must be done to avoid negative traits in acting, what is important is openness in any aspect of marriage. 5. Equality There is a change in attitude after marriage, more assertive, protective and caring for the family, both from the husband and the wife, there was no difference in attention that is differentiated from one another